Effects of Giving Alfamangios on Cholesterol Levels and Pancreatic Appearance in Diabetes Mellitus Induced Rats : Efek Pemberian Alfamangios Terhadap Kadar Kolesterol Dan Gambaran Pankreas Pada Tikus Terinduksi Diabetes Mellitus - Kardina, Rizki Nurmalya; Santoso , Andreas Putro Ragil; Putri, Fildzah Karunia; Murtasiyah, Erna Dwi; Arif, Sheila Weni Astuti (Universitas Muhammadiyah Sidoarjo, 2021)
The isolate compound α-Mangostin was the most dominant compound found in the rind and trunk of the mangosteen fruit tree (Garcinia mangostana L.). These compounds are reported to have many pharmacological activities such as antibacterial, antifungal, antidiabetic, anti-cancer and several other bioactivities. The aim of this research was to measure the activity of α-Mangostin isolate using 13C and 1H NMR and to find out whether this compound had bioactivity on pancreatic physiology and histopathology in type II diabetes mellitus rats with the parameters measured were cholesterol and pancreatic histopathology. This research was conducted at the Laboratory of the Faculty of Veterinary Medicine, Airlangga University, Surabaya. This research is a true experimental type because the data were taken through laboratory tests with the treatment of the research sample. The sample in this study were rats with induced diabetes mellitus. 30 rats were separated into 5 groups for each group of 6 rats. The results of this study There are differences in the effect of giving alpha mangiostin on blood cholesterol levels in rats that have been induced by diabetes mellitus, and there is a change in the morphology of the pancreas caused by free radicals.